Examining the dynamics of mobile banking app. Adoption during the COVID-19 pandemic: A digital shift in the crisis - Mahfuzur Rahman; Hew Pow Yee; Md. Abdul Kaium Masud; Md Uzir Hossain Uzir (Digital Business, 2024)
Mobile banking applications (apps) have become crucial in maintaining financial services accessibility during the COVID-19 pandemic. This study leverages the Unified Theory of Acceptance and Use of Technology (UTAUT) to examine Malaysian millennials' behavioral intentions toward mobile banking app adoption, aiming to aid banks in developing targeted strategies to expand their user base. Data collection was conducted from October 2020 to February 2021 during the peak of the COVID-19 pandemic. A survey was administered to 270 respondents using convenience and snowball sampling methods. The Sequential Least Square method was used for the analysis. Our findings reveal that performance expectancy, effort expectancy, trust, and personal innovativeness significantly influence mobile banking app adoption intentions, whereas social influence and facilitating conditions do not. Demographic factors also modulate these relationships to varying degrees. These insights contribute to theoretical discussions on technology adoption and offer practical guidance for banks looking to enhance their digital service offerings in a post-pandemic landscape. This study underscores the shifts in consumer behavior triggered by the pandemic and highlights the ongoing potential for digital banking growth in Malaysia.
Keywords: D91; O33; L86; 650; Behavioral intention; COVID-19; Millennials; Mobile banking app; Technology adoption